ANALYSIS OF PROMOTIONAL ACTIONS TAKEN BY AGROTOURISTIC FARMS ON MIDDLE POMERANIA - Marczak, Mirosław; Borzyszkowski, Jacek (Acta Scientiarum Polonorum. Oeconomia, 2010)
Middle Pomerania is the area marked by high-end values of the natural origin, development-friendly rural tourism, especially agrotourism. For the analysis area currently operates dozens of farms that offer the wider agrotourism services. Their offer is very diverse, tailored to the requirements of various segments of the target audience. The paper presents such prospects for further development of this form of tourism, taking into account the suitability test under the area of options and different types of barriers to this development. Offer surveyed households are shown in the context of marketing, taking into account in the analysis of individual elements of the tourist product (including the core product, the actual product expanded). The paper also characterizes promotional actions undertaken in recent years by the owners (including promotion instruments, financial outlays for promotion).